A. V. Solovyev. Parasa Moore auct.: phylogenic review of the complex from the Palaeartic and Indomalayan regions (Lepidoptera, Limacodidae) - A. Vives Moreno (SHILAP, 2022)
Revisión de "Parasa Moore auct.: phylogenic review of the complex from the Palaeartic and Indomalayan regions (Lepidoptera, Limacodidae)" de A. V. Solovyev